THE ROLE OF EXTENSIFICATION IN PLASTIC EXCISE SEGMENTATION TO REDUCE CONSUMPTION AND INCREASE STATE REVENUE: A SUSTAINABLE WASTE MANAGEMENT PERSPECTIVE - Fatih Naufal; Antonius Bimo Rentor Luntungan; Melania Lintang Kenisah (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Indonesia faces significant challenges in managing plastic waste. Projections from the National Waste Management Information System (SIPSN) estimate that national waste generation will reach 50.06 million tons in 2025, with around 40 percent remaining unmanaged and entering the ocean. Each year, approximately 16.02 million tons of waste flow into Indonesian waters, threatening marine ecosystems. Despite waste management budget realization reaching IDR 61.86 billion in 2024 and absorption levels consistently exceeding 99 percent, environmental outcomes remain suboptimal. This condition highlights the need for stronger fiscal instruments that ensure administrative efficiency and directly reduce plastic consumption and improve environmental performance. Previous studies on plastic excise in Indonesia have generally applied uniform tax rates without considering segmentation based on product categories or environmental impact. In addition, research addressing excise as a dual fiscal–environmental instrument remains limited. This study aims to examine the role of extensification in segmented plastic excise as a more proportional alternative to conventional approaches. This research employs a qualitative policy analysis approach, supported by a comparative review of international practices in plastic taxation. The findings indicate that uniform excise rates are less effective in addressing varying environmental impacts across plastic products. A segmented excise system, based on product characteristics and environmental impact, is more effective in influencing consumption behavior while expanding fiscal capacity. This study contributes by proposing an extensification-based segmentation model that integrates environmental objectives with fiscal policy, providing practical insights for policymakers in designing more adaptive and sustainable plastic excise policies in Indonesia.